Ecophysiological modeling of photosynthesis and carbon allocation to the tree stem in the boreal forest - Gennaretti, Fabio; Gea-Izquierdo, Guillermo; Boucher, Etienne; Berninger, Frank; Arseneault, Dominique; Guiot, Joel (Biogeosciences, 2017)
A better understanding of the coupling between photosynthesis and carbon allocation in the boreal forest, together with its associated environmental factors and mechanistic rules, is crucial to accurately predict boreal forest carbon stocks and fluxes, which are significant components of the global carbon budget. Here, we adapted the MAIDEN ecophysiological forest model to consider important processes for boreal tree species, such as nonlinear acclimation of photosynthesis to temperature changes, canopy development as a function of previous-year climate variables influencing bud formation and the temperature dependence of carbon partition in summer. We tested these modifications in the eastern Canadian taiga using black spruce (Picea mariana (Mill.) B.S.P.) gross primary production and ring width data. MAIDEN explains 90% of the observed daily gross primary production variability, 73% of the annual ring width variability and 20-30% of its high-frequency component (i.e., when decadal trends are removed). The positive effect on stem growth due to climate warming over the last several decades is well captured by the model. In addition, we illustrate how we improve the model with each introduced model adaptation and compare the model results with those of linear response functions. Our results demonstrate that MAIDEN simulates robust relationships with the most important climate variables (those detected by classical response-function analysis) and is a powerful tool for understanding how environmental factors interact with black spruce ecophysiol-ogy to influence present-day and future boreal forest carbon fluxes.